The Correlation Between Students' Spiritual Care Abilities And Patient Satisfaction - ISNAWATI, IIN AINI (Journal of health research and technology, 2026)
Background: Spiritual nursing training is one way to improve nursing students' abilities in providing spiritual nursing care to patients. After conducting training using the santri method, there was a proven increase in spiritual intelligence and spiritual care competence. The purpose of this study was to identify the correlation between students' spiritual care abilities and patient satisfaction during their treatment by previously trained nursing students. Methods: This cross-sectional study was conducted on 75 student nursing and 75 patients treated by nursing students, selected through simple random sampling. Data collection tools consisted of questionnaires on satisfaction with spiritual nursing care. The data obtained were analysed using SPSS 20 with descriptive and inferential statistics. Results: The results showed that the average spiritual care ability of students was 119.3 and the average patient satisfaction was 39.4. After performing a correlation test, a p-value of 0.000 was obtained, indicating that there is a significant correlation between students' ability to provide spiritual care and patient satisfaction. Conclusion: The results of this study indicate that there is a correlation between the spiritual care abilities of nursing students and patient satisfaction, and that the higher the level of clinical spiritual care abilities, the greater the patient satisfaction in hospitals. Therefore, nursing institutions and health system administrators should provide santri model training to improve the spiritual care of nursing students and develop their spiritual care competencies in order to increase patient satisfaction.